The Impact of Sustainable Development as a Moderating Variable in the Relationship Between Financial Performance and Market Value - Pasaribu, Hasudungan Edward Reinra; Triantoro, Ilham Gayuh; Muchtar, Susy (Amkop Management Accounting Review (AMAR), 2025)
This study aims to examine the impact of accounting information (Earnings per Share and Book Value per Share), debt financing (short-term and long-term debt), asset investment (current and fixed), and dividend payout ratio on firm market value, while considering sustainable development (SD), measured through ESG index participation, as a moderating variable. The research uses a sample of manufacturing firms listed on the Indonesia Stock Exchange (IDX) during 2022–2024, selected through purposive sampling based on consistency in reporting and dividend distribution. Data were obtained from annual financial reports and sustainability reports and analyzed using E-Views software. The findings indicate that EPS and BVPS significantly influence market value, but this effect weakens when ESG engagement is taken into account. Short- and long-term debt financing show a negative association with market value, while fixed asset investment and dividend payout have positive impacts. Furthermore, sustainable development plays a moderating role in strengthening or weakening the relationship between financial variables and market value. These results highlight the importance of firms integrating sustainability into their financial strategies and investment decisions to enhance long-term market value and investor confidence.